The town planning congresses at the Paris International Exhibition of 1937: Ultimate encounters - Jaquand, Corinne (International Planning History Society Proceedings, 2018)
1937 is an excellent focal point to look at the international planning movement on the eve of the Second World War. Indeed, the International Exhibition of Paris has hosted several congresses devoted to urban planning in the world. Dealing with regional planning, the International Federation for Housing and Town Planning (IFHTP) held its 15th congress, while the CIAM 5, dedicated to “Logis et loisirs” (Dwelling, recreation) was organised by Le Corbusier in connection with an exhibition at the Pavillon les Temps nouveaux. This contribution proposes to present the relations between both congresses in the thirties. Emphasis will be put more on the convergences than on the divergences of topics carried out by the experts of the IFHTP and by the avant-garde architects of the CIAM, at a time when planning and politics were challenged by the rise of fascism and the threat of a world conflict.